Organic-inorganic nanocomposite organogel with double-network topology for enhanced mechanical and dielectric properties - Dongdong Yan; Shilei Zhu; Hongyao Zhao; Shanhao Feng; Beibei Kang; Xin Yang; Yanjing Zhang; Zhuangzhuang Li; Wenwen Yu; Ya Nan Ye (Supramolecular Materials, 2025)
Conventional artificial nanocomposites often rely on simple blending, which can lead to agglomeration and interfacial incompatibility between the organic and inorganic phases. In contrast, natural mineralized tissues like bone and teeth exhibit outstanding mechanical performance through nanoscale, interpenetrating organic-inorganic networks. Inspired by these naturally integrated architectures, we report a double-network (DN) organic-inorganic organogel composite formed by topologically interweaving self-assembled polyoxometalate sub-nanowires (SNWs) with a poly(tert‑butyl acrylate) (PtBA) matrix. The SNWs feature sub-nanometer diameters and flexibility similar to polymer chains, enabling them to form an inorganic network that seamlessly integrates with the organic phase. This continuous, interpenetrating DN structure enhanced key mechanical properties—including tensile strength, stiffness, and toughness—while simultaneously regulating dielectric properties such as dielectric permittivity and electrical breakdown strength, yielding a versatile, multifunctional platform. Overall, this design strategy paves the way for bioinspired advanced materials that merge mechanical robustness with customizable functionalities derived from inorganic components, promising applications in flexible electronics and functional structural materials.